AN ADAPTIVE POWER SYSTEM STABILIZER BASED ON FOCUSED TIME DELAY NEURAL NETWORK - Widi Aribowo (Jurnal Teknosains, 2017)
In this paper, Power System Stabilizer is designed in Single Machine Infinite Bus (SMIB) and speed control is implemented with a dynamic topology based on Focused Time Delay Neural Network (FTDNN).  In case of prediction and control, two individual strategies are concerned for the current projects. The first is identification the dynamics of system. The other is an optimization unit expected for minimization disturbances. The performance of the system with FTDNN-PSS controller is compared with a Conventional PSS (C-PSS), RNN-PSS and DTDNN PSS. The results show the effectiveness of FTDNN-PSS design, and superior robust performance for enhancement power system stability compared to Conventional PSS with different cases.